Intensi Berwirausaha Pada Mahasiswa Baru - Mintarti Rahayu; Lily Hendrasti Novadjaja; Nur Khusniyah Indrawati (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The aim of this research is to investigate the entrepreneurial intention of the first-year university students and also the factors that influence the intention. The Liñán’s model as an application of the TPB (Theory of Planned Behavior) was used and the data were analysed with SEM (Structural Equation Modeling). The sample is 162 first-year students of the Management Department of Economics Faculty of Brawijaya University in East Java, Indonesia, who attended the course when the survey was conducted and also willing to complete the questionairs. The findings show that the entrepreneurial intention is directly and positively affected by the attitude toward start-up and the perceived behavioral control. The subjective norm does not directly influence the entrepreneurial intention but indirectly and positively influence the intention through the attitude and the perceived behavioral control. Keywords: Entrepreneurial intentions, first-year university students, Theory of Planned Behavior